Joseph Elder (ed.), Lectures in Indian Civilization, Willard L. Johnson, Christopher R. King, Kendall/Hunt Publishing Company, Dubuque, Iowa, 1970. 453 pp. - B. A., E. (Estudios de Asia y África, 1971)
-